Studies on the Utilization of Eucalyptus Hybrid for the Manufacture of Weft-pirns for Automatic Cotton Looms - Jain, V. K.; Pandey, C. N.; Arora, K. L. (Indian Forester, 1992)
The indigenous woods for weft-pirn making have been selected on the basis of available physical, mechanical and wood-working properties. In this report, physical, mechanical and wood-working properties of Eucalyptus hybrid are compared with those of the timbers given in IS: 4417-1967. Data on actual manufacturing trial indicated that Eucalyptus can be utilised for weft-pirn making. Weft-pirns made from Eucalyptus from two different sources appeared comparable with those made from white-cedar and resistance to moisture was within permissible limits. Sawing and seasoning technique for Eucalyptus wood are also discussed.